Relative age effect and ACTN3 R577X and ACE I/D polymorphisms in Brazilian football players: An association genetic study - Albuquerque, M. R.; da Silva Cunha, A. E.; de Araújo, J. L. F.; dos Santos Guimarães, R.; Rocha, M. R. C. C.; Mesquita, P. H. C.; Pimenta, E. M.; de Souza, R. P. (Research Quarterly for Exercise and Sport, 2025)
The Relative Age Effect (RAE) suggests older athletes within an annual cohort have advantages over their younger peers. We hypothesized that younger athletes could overcome these disadvantages through favorable a-actinin-3 (ACTN3) and angiotensin converting enzyme (ACE) polymorphisms. This study aimed to: 1) examine RAE prevalence among Brazilian football players; 2) investigate the distribution of the ACTN3 and ACE polymorphisms; and 3) explore the association between polymorphisms and RAE across competitive levels and positions. The sample included 627 male players from first-division Brazilian teams in four age categories: U15 (n = 172), U17 (n = 166), U20 (n = 161), and Professionals (n = 128). A control group was established using data from the general Brazilian population documented in previous studies Results showed RAE presence across all competitive levels and positions. Players with the ACTN3 R allele, especially the RR genotype, had the strongest associations with football players, particularly among defenders. On the other hand, the distribution of ACE polymorphism was not significantly different between controls and players, except in the U17 category, where the I/I genotype was more common. Relatively older players had higher total genotype scores than younger counterparts in the overall sample and defender subgroups. In conclusion, RAE is prevalent among Brazilian football players, with older athletes benefiting from favorable ACTN3 and ACE polymorphisms, contrary to our initial hypothesis.